2017
DOI: 10.3390/ijms18030654
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Loads and Genotypes of Respiratory Syncytial Virus: Viral Factors during Lower Respiratory Tract Infection in Chilean Hospitalized Infants

Abstract: Abstract:The clinical impact of viral factors (types and viral loads) during respiratory syncytial virus (RSV) infection is still controversial, especially regarding newly described genotypes. In this study, infants with RSV bronchiolitis were recruited to describe the association of these viral factors with severity of infection. RSV antigenic types, genotypes, and viral loads were determined from hospitalized patients at Hospital Roberto del Río, Santiago, Chile. Cases were characterized by demographic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
1
13
1
Order By: Relevance
“…Although some authors have found no correlation between subtypes and disease severity [32,33], many others indicate RSV-A as the most virulent subtype [9,10,12,34,35]. We have…”
Section: The Subtype But Not the Viral Load Appears To Be Associated With Disease Severitycontrasting
confidence: 52%
See 1 more Smart Citation
“…Although some authors have found no correlation between subtypes and disease severity [32,33], many others indicate RSV-A as the most virulent subtype [9,10,12,34,35]. We have…”
Section: The Subtype But Not the Viral Load Appears To Be Associated With Disease Severitycontrasting
confidence: 52%
“…Some studies found an association between viral load and symptom frequency, but not severity itself [39,40]. Viral load measurement methods are widely variable between studies: some authors use plaque assay [4] or semi-quantitative analyses, such as ct [5,7,32], others use quantitative methods [38][39][40][41]. Moreover, most studies that use quantitative methods do not normalize the measurements.…”
Section: Plos Onementioning
confidence: 99%
“…The RSV strains and S. pneumoniae molecular serotypes identified within this cohort are consistent with global circulation patterns from around the time of the study period [43–45]. RSV genotype GA2 was the most highly prevalent strain, followed by BA and GA5.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, RSV strains circulating in Lao PDR were characterized for the first time, with the detection of the common genotypes of RSV‐A NA1, RSV‐B BA9, and the rare CB1/THB genotype. Cocirculation of different genotypes in a country during RSV season is not uncommon . Most RSV genotypes are often shared between various regions of the world.…”
Section: Discussionmentioning
confidence: 99%